Lung perfusion MRI after congenital diaphragmatic hernia repair in 2-year-old children with and without extracorporeal membrane oxygenation therapy - Weis, Meike; Zöllner, Frank G.; Henzler, Claudia; Schönberg, Stefan; Zahn, Katrin; Schaible, Thomas; Neff, Wolfgang (American journal of roentgenology, 2016)
Objective: In severe cases of congenital diaphragmatic hernia (CDH), extracorporeal membrane oxygenation (ECMO) therapy improves survival. Later on, lung morbidity mainly defines development. The purpose of this study was to investigate whether 2-year-old children who need ECMO therapy after delivery have reduced perfusion MRI values as a sign of more severe lung hypoplasia than do children who do not need ECMO. Materials and methods: After CDH repair, 38 children underwent dynamic contrast-enhanced MRI with a 3D time-resolved angiography with stochastic trajectories sequence. Fifteen (39%) of the children had received ECMO therapy in the neonatal period. Pulmonary blood flow (PBF), pulmonary blood volume (PBV), and mean transit time were calculated for both lungs. In addition, the ratio of ipsilateral to contralateral lung was calculated for all parameters. Results: In all children, those with and those without ECMO requirement, PBF and PBV were significantly reduced on the ipsilateral side (p < 0.05). Children who had received ECMO therapy had significantly reduced PBF and PBV values on the ipsilateral side (p < 0.05) compared with children who had not needed ECMO therapy. The ratios of ipsilateral to contralateral lung for PBF and PBV were also significantly reduced after ECMO. Conclusion: Two-year-old children undergoing CDH repair who had needed neonatal ECMO had significantly reduced perfusion MRI values in the ipsilateral lung in comparison with children who had not needed ECMO. Perfusion MRI measurements are associated with the severity of lung hypoplasia and may therefore be helpful in follow-up investigations.